Penerapan Terapi Bermain Papan Kancing Terhadap Kemampuan Motorik Halus Mengancing Baju Anak Tunagrahita Sedang di SLB Bhakti Luhur Maumere - Theresia Nona Megi; Yosefina Nelista (Lembaga Pengembangan Kinerja Dosen, 2026)
Children with intellectual disabilities experience limitations in intellectual functioning and adaptive abilities, which impact their independence in daily activities, including buttoning clothes. This skill requires fine motor coordination, concentration, and a proper understanding of task sequences. This case study aims to determine the effectiveness of button board play therapy in improving fine motor skills in children with intellectual disabilities. The method used was descriptive with a case study approach involving two children with moderate intellectual disabilities aged 8 and 9 years at SLB Bhakti Luhur Maumere. Data were collected through interviews, observations, and documentation. The intervention consisted of button board play therapy conducted for 6 days, with a duration of 15–30 minutes per day, implemented gradually and repeatedly. The results showed that before the intervention, both children were unable to button their clothes independently. After the intervention, there was an improvement in their ability, as the children began to button some buttons (2–3 buttons) with better motor coordination, although they still required assistance and supervision. In conclusion, button board play therapy is effective in gradually improving fine motor skills and independence in children with intellectual disabilities. It is recommended that the intervention be carried out consistently and involve parents to achieve optimal results.